2014
DOI: 10.1016/j.jamda.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directive and End-of-Life Care Preferences Among Nursing Home Residents in Wuhan, China: A Cross-Sectional Study

Abstract: Objectives: To describe Chinese nursing home residents' knowledge of advance directive (AD) and end-oflife care preferences and to explore the predictors of their preference for AD. Design: Population-based cross-sectional survey. Settings: Nursing homes (n ¼ 31) in Wuhan, Mainland Southern China. Participants: Cognitively intact nursing home residents (n ¼ 467) older than 60 years. Measures: Face-to-face questionnaire interviews were used to collect information on demographics, chronic diseases, life-sustaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 25 publications
6
68
6
Order By: Relevance
“…Although other studies have found that a family member was the most common person to communicate with about ADs in patients in countries with East Asian cultures [28,29], this study indicated that participants tended to regard medical staff as the optimal role to communicate with about ADs. This conclusion also supports the findings of previous studies [30,31,32].…”
Section: Discussioncontrasting
confidence: 73%
“…Although other studies have found that a family member was the most common person to communicate with about ADs in patients in countries with East Asian cultures [28,29], this study indicated that participants tended to regard medical staff as the optimal role to communicate with about ADs. This conclusion also supports the findings of previous studies [30,31,32].…”
Section: Discussioncontrasting
confidence: 73%
“…preferred to make ADs; this result is inconsistent with a previous study showing that 22.4% of patients with cancer approved of ADs [7]. This discrepancy may be attributed to the fact that in the previous study, the participants originated from different regions of China with different cultures and had different types of cancer.…”
Section: Discussioncontrasting
confidence: 77%
“…Chinese communities around the world have a low engagement with ACP services (Con, 2007; Cultural & Indigenous Research Centre Australia (CIRCA), 2008, Gao, Sun, Ko, Kwak, & Shen, 2015;Ni et al, 2014;Ting & Mok, 2011;Yonashiro-Cho et al, 2016). The reasons for this are generally attributed to cultural considerations including taboos related to end-of-life consideration and the role of the collective family in decision-making or logistical considerations including health literacy, language and access to health services.…”
Section: Discussionmentioning
confidence: 99%